Burnout among clinicians in tertiary care setting - Chepuru, Rajya Lakshmi; Lotheti, Siva Kumar; Bhimarasetty, Devi Madhavi (International Journal Of Community Medicine And Public Health, 2018)
Background: “Burnout” is defined as a state of physical, emotional and mental exhaustion, or a coping mechanism to working conditions that are stressful, demanding and lack of recognition. Effects of burnout are many and can eventually threaten one’s job satisfaction, relationship and also health. High patient load, long working hours, poor logistics and infrastructure support and unreasonable demands from patients make clinicians vulnerable for stress and burnout. Objective was to study the prevalence of burn out in clinicians and factors associated with burnout. Methods: The study was an observational descriptive cross-sectional study conducted among Doctors in clinical departments of a Tertiary Medical care setting in October-November 2015. Sample size was 97. Study was conducted using Maslach Burnout Inventory with additional questions on demographic factors, work experience, hours of work and speciality. The inventory comprised 22 items on a seven-point Likert scale. Frequency of symptoms (ranging from ‘0=never’ to ‘6=every day’). Burnout was measured in three dimensions - emotional exhaustion (EE), depersonalization (DP) and personal accomplishment (PA). The data was collected after taking Institutional ethics committee approval and verbal consent from participants. Data was analyzed using MS Excel 2007. Results: About 15% 0f clinicians showed high emotional exhaustion, 9% high depersonalization, and 18% low Personal accomplishment. More Females showed burnout than males and more clinicians from surgical branches showed burnout when compared to medical branches. Conclusions: Burnout exists among healthcare professionals and measures should be taken to identify causes and take remedial actions.